Kinetic Aspects of the Oxidation of Perfumery Phenols by n-Bromosuccinimide in Alkaline Medium, Potassium Bromate and Potassium Iodate in Acidic Medium - Prabhu, D.V.; Tandel, M.A.; Parbat, H.A.; H. Uchil, Meera (Asian Journal of Chemistry, 2012)
The isomeric phenols eugenol and isoeugenol are used in the formulation of perfumes. Not much work has been reported on the kinetic and thermodynamic aspects of the oxidation of these perfumery phenols. The kinetic studies of the oxidation of phenols to o-quinones have been carried out using (1) N-bromosuccinimide in alkaline medium and (2) inorganic oxidants KBrO3 and KIO3 in acidic medium. The oxidation was carried out using pseudo first order kinetics with respect to the oxidizing agent. The effects of phenol and oxidant concentrations, ionic strength and temperature (303-318 K) on the oxidation rate have been studied in detail. For all the oxidizing agents under study, the oxidation rates of phenols follow the sequence isoeugenol > eugenol which has been explained on the basis of structures, steric factors and isomeric characteristics of the phenols. Suitable reaction mechanisms have been suggested for the oxidation of the phenols to o-quinones.